Song «Fly, Fly, Cuckoo» as a Phenomenon of Musical and Poetic Work of the Chuvash People - Alisa L. Agakova (Publishing house "Sreda", 2020)
The article examines the semantic and axiological foundations of «Fly, fly, cuckoo» - the most popular work of Chuvash song folklore. The purpose of the work is to establish the history of the song from the moment of the first recording and analyze its professional processing. The author practices a short generalized description of the most characteristic features of each artistic treatment. This approach allows to clearly feel the individual handwriting of each composer. The research results are based on comparison and generalization methods. The melody of this song inspired the Chuvash and Russian composers to create works of different genres: vocal, choral, instrumental. It is unique in terms of the number of adaptations: there are more than 30 of them - so often composers did not pay attention to any Chuvash song. The article discusses the most vivid and characteristic examples of processing the melody of a song. The author analyzes the works of S. M. Maksimov, A. G. Orlov-Shuzm, G. Khirbyu, A. Petrov, G. Anchikov, V. Bely and others. The inclusion in the educational process of such examples of folk art as the song «Fly, fly, cuckoo», and works created on this topic, contributes to an increase in the level of musical culture, the formation of respect for indigenous peoples and their traditions.